Stalin and the Soviet Union - Lee, Stephen J., 1945- (Questions and analysis in history., 1999)
Stalin and the Soviet Union offers new interpretations of recently uncovered archives examining the Soviet leader's domestic and foreign policy. It covers core topics such as: * Stalin's rise to power* the economy* society* culture* the Cold War* the Second World War* terror. For all students of Russia, Stalin and European history, this will prove essential reading, and a clear background and guide to exam success.